0
$\begingroup$

After solving a probability question I ended up with the following:

$P(A)=\frac{1}{6}\sum\limits_{n=1}^\infty(\frac{5}{6})^{3n-2}$ limit between 1 and infinity but I'm unsure how to carry this on , I am familiar with summing $x^n$ to infinity for modulus X less than one . Sorry if this is a easy question, any help would be great thanks.

$\endgroup$
  • $\begingroup$ which are the limits of sum? $\endgroup$ – Martín Vacas Vignolo May 6 '18 at 19:48
  • $\begingroup$ 1 to infinity not sure how to add limits to summation sorry $\endgroup$ – user528906 May 6 '18 at 19:51
  • $\begingroup$ For the next time, \sum\limits_{lower bound}^{upper bound} $\endgroup$ – Martín Vacas Vignolo May 6 '18 at 20:12
  • $\begingroup$ @MartínVacasVignolo got it! thanks for your answer btw $\endgroup$ – user528906 May 6 '18 at 20:19
1
$\begingroup$

You may write $$ \begin{align} \frac16\sum_{x=1}^\infty \left(\frac{5}{6}\right)^{3x-2}&= \frac16 \cdot \left(\frac{5}{6}\right)^{-2}\sum_{x=1}^\infty \left(\frac{5}{6}\right)^{3x} \\\\&= \frac16 \cdot \frac{36}{25}\sum_{x=1}^\infty \left(\frac{5^3}{6^3}\right)^{x} \\\\&=\frac{6}{25}\sum_{x=1}^\infty \left(\frac{125}{216}\right)^{x} \\\\&=\frac{6}{25}\cdot\frac{125}{216} \sum_{x=1}^\infty \left(\frac{125}{216}\right)^{x-1} \\\\&=\frac{5}{36} \sum_{x=0}^\infty \left(\frac{125}{216}\right)^{x} \end{align} $$ by a change of index.

Hope you can finish it using $$ \sum_{x=0}^\infty q^{x}=\frac 1{1-q},\quad|q|<1. $$

$\endgroup$
  • $\begingroup$ Thanks a lot :), didn't spot that so dumb of me. $\endgroup$ – user528906 May 6 '18 at 20:03
  • $\begingroup$ @Edwnhazard You are very welcome. $\endgroup$ – Olivier Oloa May 6 '18 at 20:04
0
$\begingroup$

I will use the fact that $\sum\limits_{n=0}^\infty p^n=\frac{1}{1-p}$ if $|p|<1$.

Now,

$\begin{align*} \frac{1}{6}\sum\limits_{n=1}^\infty (\frac{5}{6})^{3n-2} &= \frac{1}{6}\left(\sum\limits_{n=1}^\infty (\frac{5}{6})^{3n}\right)(\frac{5}{6})^{-2}\\ &= \frac{6}{25} \left(\sum\limits_{n=1}^\infty [(\frac{5}{6})^3]^{n}\right)\\ \end{align*}$

Now put $p=(\frac{5}{6})^3$.

We have $\frac{6}{25}\sum\limits_{n=1}^\infty p^n=\frac{6}{25}\left(\sum\limits_{n=0}^\infty p^n-p^0\right)=\frac{6}{25}\left(\frac{1}{1-p}-1\right)=\frac{6}{25}\frac{p}{1-p}=\frac{6}{25}\frac{(\frac{5}{6})^3}{1-(\frac{5}{6})^3}$

$\endgroup$
0
$\begingroup$

It is a decreasing geometric progression with $q=\left(\frac56\right)^3<1$: $$\frac16\sum_{x=1}^\infty \left(\frac{5}{6}\right)^{3x-2}=\frac16\left(\frac56+\left(\frac56\right)^4+\left(\frac56\right)^7+\cdots\right)=\frac16\cdot \frac{\frac56}{1-\left(\frac56\right)^3}=\frac{30}{91}.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy